Is there a relationship between the morphological characteristics of developmental venous anomalies and the presence of parenchymal abnormalities? - Şirin Özcan, Ayşe Nur; Hasanov, Behruz; Unal, Ozlem (The European Research Journal, 2021)
Objectives: Developmental venous anomaly (DVA) is a benign vascular malformation. Hyperintensity in the fluid-attenuated inversion recovery (FLAIR) sequence in the adjacent white matter has been previously identified. Although there are different theories, it is not yet clear why these hyperintensities occur. In this study, we aimed to investigate the factors affecting hyperintensity formation by examining the relationship between the morphological findings of DVA and the presence of FLAIR hyperintensity. Methods: The study included 84 cases diagnosed with DVA. Patients with susceptibility weighted imaging (SWI) and/or postcontrast T1-weighted sequences in addition to conventional MRI sequences were included. The patients were divided into two groups as hyperintensity FLAIR (+) and FLAIR (-) in the examination performed around DVA. There were 24 patients in the FLAIR (+) group and 60 patients in the FLAIR (-) group. The localization of DVAs, drainage localization of the intramedullary vein, collector vein diameter, collector vein length, DVA location depth, and patient ages were compared between the two groups. Results: When examining the relationship between the groups and variables in the statistical evaluation, there was no difference between the groups in terms of DVA localization, the venous system of drainage, DVA depth, and the length of the collector vein. However, a significant difference was observed between the groups in terms of the collector vein diameter and age. Conclusions: The results of this study indicating a relationship between collector vein diameter and patient age. The relationship between this diameter and age suggests that there is a correlation between the degree and duration of venous congestion and the change in white matter.